Moral superiority over the state: Young people’s experience of inflation and the rise of the libertarian right in Argentina - Welschinger Lascano, Nicolás Sebastían (2025)
This article examines social experiences of inflation as the basis for an empirical analysis about how a particular sector in Argentina began leaning toward the political platform of the extreme right under Javier Milei. In order to establish these connections, we focus on the experience of young people, as this is the age group where support for the libertarian is broadest. The research included a quantitative and a qualitative stage (surveys and focus groups) in order to grasp the experience of crisis among lower and middle-class urban youth in neighborhoods of the Buenos Aires Metro Area. It traces the period from 2020, when inflation began to surge, to the presidential elections of 2023, showing how the experience of inflation among Argentine youth contributed to a moral antagonism toward the state. This, in turn, fostered a sense of moral superiority among this age group that led them to embrace the libertarian political platform, especially the dollarization of Argentina’s economy.